THEORETICAL CONTENT FOUNDATION OF PREPARING TEACHERS OF LABOR TRAINING TO TEACHING BASIS OF DESIGN - Ihor Savenko (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
In the article the basic principles of shaping the content of training future teachers of technology education to realize design activity in schools have been considered. Formation of the basic core knowledge, abilities and skills of future teachers should be provided in the fundamental scientific, general and cultural and professional training that is subjected to certain principles of pedagogical design. Design education as a powerful educative potential aimed at designing and providing humanitarian and cultural orientation of a student has been revealed. The design is a valued feature of professional education of future teachers of labor studies and promotes the development of a special type of culture and thinking that directs to educational values and determines the individual educational strategy of professional development.